The Effect of Organizational Justice on Organizational Commitment in the Public Universities in Amhara Region - Teshome, Shimelis Mesfin; Bitew, Getnet Demissie; G/meskel, Tilahun Gidey (Bahir Dar Journal of Education, 2022)
The purpose of this study was to examine the effect of organizational justice (OJ) on organizational commitment (OC) in the public universities of Amhara region. Descriptive survey design was employed. The size of the population was 2170. Of these, 900 instructors were selected using stratified and simple random sampling techniques. Standardized questionnaire was used to collect the data. The collected data were analyzed using one sample t-test, Structural Equation Modeling and one way analysis of variances (ANOVA). The result of one sample t-test indicated that instructors perceived the state distributive justice fairly, while they perceived procedural and interactional justice to a little extent in the workplace. With regard to OC, instructors were moderately committed to carry out their jobs due to their emotional attachment with their universities and sense of responsibility to serve their universities. There was positive and statistically significant relationship between OJ and OC with standardized correlation coefficient (r=.766) by the critical ratio test greater than Â±1.96 at p<.05. The value of R-squared indicated that 58.7 % of the variance in OC was predicted by OJ with standardized regression coefficient (r =.766) at p<.05. With regard to variation, the result of one way ANOVA indicated that statistically significant differences were observed among instructors in their perception of OJ at F (3,788) = 54.289 and OC at F(3, 788) = 35.950 at p<.05 on the basis of the four generations of universities. Based on the finding of this study, it is concluded that OJ had significant effect on OC even if some of its dimensions were observed to a little extent in the workplace. Therefore, it is suggested to improve the current status of OJ and OC in the respective universities to make instructors feel good about their job and committed to carry out their duties effectively.